2009
DOI: 10.1007/s11803-009-9115-3
|View full text |Cite
|
Sign up to set email alerts
|

Optimal design theories of tuned mass dampers with nonlinear viscous damping

Abstract: Optimal design theory for linear tuned mass dampers (TMD) has been thoroughly investigated, but is still under development for nonlinear TMDs. In this paper, optimization procedures in the time domain are proposed for design of a TMD with nonlinear viscous damping. A dynamic analysis of a structure implemented with a nonlinear TMD is conducted fi rst. Optimum design parameters for the nonlinear TMD are searched using an optimization method to minimize the performance index. The feasibility of the proposed opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(34 citation statements)
references
References 21 publications
1
33
0
Order By: Relevance
“…The previous section has shown that the displacement reduction of the main structure is not very sensitive to the damping coefficient of the nonlinear viscous damper employed in the TVMD, which is in agreement with the results in Chung et al for nonlinear TMD under wind excitations. In this section, the sensitivity of the maximum DMF of the main structure to the intensity of the external excitations is analyzed.…”
Section: Optimal Design Of Tvmd With Nonlinear Fluid Viscous Dampingsupporting
confidence: 90%
See 1 more Smart Citation
“…The previous section has shown that the displacement reduction of the main structure is not very sensitive to the damping coefficient of the nonlinear viscous damper employed in the TVMD, which is in agreement with the results in Chung et al for nonlinear TMD under wind excitations. In this section, the sensitivity of the maximum DMF of the main structure to the intensity of the external excitations is analyzed.…”
Section: Optimal Design Of Tvmd With Nonlinear Fluid Viscous Dampingsupporting
confidence: 90%
“…The GVB system has the same mathematical model as the TVMD, and their results showed that the GVB system with nonlinear viscous damper has less requirement of the damping coefficient but can obtain nearly the same control performance as the GVB system with linear viscous damper. On the other hand, the performances of the TMD with nonlinear viscous damper attached to SDOF system or multiple degree‐of‐freedom system under white noise excitations or wind loads have been carefully studied . The results indicate that the damping exponent of the nonlinear viscous damper has a great influence on the optimal damping coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…However, they suffer the drawback of not being functional at low‐frequency wind excitations. Hence, for mitigation of wind‐induced vibrations in a full‐scale structure, linear and nonlinear VDs have been implemented either in large numbers (as elucidated in Sections and ) or in combination with passive or active TMD/TLCDs …”
Section: Introductionmentioning
confidence: 99%
“…For example, a nonlinear hysteretic damper has been supplemented for enhanced energy dissipation [13][14][15][16][17]. Chung et al [18] demonstrated the effectiveness of such a TMD by implementation in the Taipei 101 building. These enhanced TMDs were found to be more effective than the conventional ones in a certain range of excitation frequencies.…”
Section: Introductionmentioning
confidence: 99%